2013
DOI: 10.1002/lary.23879
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone spheres and theromosensitive pluronic F127 hydrogel for vocal fold augmentation: In vivo animal study for the treatment of unilateral vocal fold palsy

Abstract: Locally injected PCL/Pluronic F127 can enhance glottal contact, suggesting it as a potential new therapeutic approach that may lead to better treatment of vocal fold palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
(60 reference statements)
2
31
0
Order By: Relevance
“…In a previous pilot study in animals, we demonstrated excellent tolerance of this bioimplant injected into the paralyzed vocal fold; no adverse reactions were observed over a 12-week follow-up period. [27] We performed the present long-term study to confirm the good results obtained in these first preclinical trials. Overall, a comparative analysis of the histological results over a period of 12 months indicated that in contrast to Radiesse®, PCL microspheres/Pluronic F127 remained more in volume at the paralyzed vocal fold, without inducing inflammation or migration.…”
Section: Discussionsupporting
confidence: 54%
“…In a previous pilot study in animals, we demonstrated excellent tolerance of this bioimplant injected into the paralyzed vocal fold; no adverse reactions were observed over a 12-week follow-up period. [27] We performed the present long-term study to confirm the good results obtained in these first preclinical trials. Overall, a comparative analysis of the histological results over a period of 12 months indicated that in contrast to Radiesse®, PCL microspheres/Pluronic F127 remained more in volume at the paralyzed vocal fold, without inducing inflammation or migration.…”
Section: Discussionsupporting
confidence: 54%
“…Endoscopic and histological analysis showed that the PCL spheres/Pluronic F127 gel mixture exhibited excellent integration with the surrounding tissues, maintained the injected volume without migration or induction of inflammatory response, decreased the vocal gap, and improved asymmetric VF movement, suggesting its potential as a new therapeutic biomaterial to treat VF paralysis. [133] In parallel, the authors investigated the effects of another synthetic and biodegradable polymer poly(lactic-co-glycolic acid) (PLGA) with Pluronic F127 mixture for the augmentation of atrophied VFs. Laryngoscopic analysis showed that both 5wt% and 10wt% PLGA/Pluronic F127 gels maintained their integrity 8 weeks after injection without inducing significant inflammatory response.…”
Section: Biomaterials In Development/researchmentioning
confidence: 99%
“…In 2013 and 2014, Kwon et al published short‐ and long‐term results of IL utilizing PCL microspheres. They were able to demonstrate excellent volume retention of material after 12 months and a small amount of inflammatory reaction to the injection in a rabbit model . Their study did not note any material migration over time in the PCL group.…”
Section: Discussionmentioning
confidence: 94%
“…Given these shortcomings, additional work to optimize injection material is warranted. Recent efforts to move toward a more ideal injectable have focused on either biological enhancement of traditional materials or use of long‐lasting synthetic biopolymers to enhance injection longevity . We hypothesized that we could create long‐lasting biomaterial using tissue‐engineering principles by utilizing a bioscaffold, a cell source, and growth factors (GFs) to create a novel, self‐sustaining biomaterial .…”
Section: Introductionmentioning
confidence: 99%